Inner-City Housing: An Exploration of Alternative Approaches for City Regeneration through the 'Housing Inclusivity Lens' - Mapiye, Karen (Department of Construction Economics and Management, 2023)
Housing unaffordability has become a common phenomenon around the globe. The rate of demand for affordable housing around inner cities has seen a rise over the past couple of decades, yet the supply has not been able to keep up and has fallen far behind. In South Africa, historically, the apartheid regulations and practices forcefully removed families of colour from inner-city areas. The current state-led housing programmes in South Africa have continued to perpetuate these apartheid policies through continuing to provide housing on the periphery of the towns and cities. The private sector, incentivised by the State's inner-city urban regeneration programmes, has inevitably accelerated spatial segregation through systematic gentrification. As a result, inner cities have become unaffordable, further distancing the previously disadvantaged from economic and social opportunities and financial participation that are concentrated within inner-city areas. There is therefore a need to consider housing inclusivity in development processes and policies and more so, practical approaches and mechanisms on how it can be implemented with inner-city developments. Concurrently, the concept of affordability needs to be explored to understand what makes inner-city housing unaffordable. This research aimed to understand the underlying causes of unaffordability in the inner cities of South Africa, particularly in Cape Town, and the roles of the public and private sectors regarding the problems and solutions. The research intended to find appropriate responses and solutions to affordable inner-city housing provision, by examination of the policies and cost drivers that affect the development process and how their negative impact can be mitigated. This study purported to aid in finding a resolve for apartheid spatial planning, whilst building a broad understanding to the key issues around gentrification, inclusivity, and the ‘right to the city' in the South African context. To identify alternative development approaches for more inclusive cities, the study made use of in-depth literature analysis and case study research which includes qualitative knowledge gained from interviews with the various role players in the housing development process. The study employed a purposive and snowball sampling method to acquire eleven participants that were interviewed. The research ascertained that the lack of policy alignment between the national government and the City of Cape Town and unrefined approval processes are aiding in increasing development costs, which are then transferred to the end-user. The research further determined that the lack of well-located affordable land possess a great challenge, yet there are large tracts of state-owned land in well located areas affordable housing development could occupy. Whilst the rest of the world moves forward in adopting alternative building technology that has advanced the industry, South Africa remains on the backfoot, though reluctancy to integrate these new methods into the traditional brick and mortar way of developments. A key recommendation is for the public sector to timeously release public-owned inner-city land that is well-located for affordable housing purposes, whilst also enabling a quicker development approval process for affordable housing projects. This amongst other interventions will serve as incentive to developers in the era of implementing the inclusionary housing policy which has stirred much controversy in its wake.